Transcranial direct current stimulation over the left dorsolateral prefrontal cortex modulates auditory mismatch negativity. Issue 5 (May 2016) - Weigl, Michael; Mecklinger, Axel; Rosburg, Timm
Highlights: Involvement of the left dorsolateral prefrontal cortex (DLPFC) in the generation of the novelty-P3, target-P3, and mismatch negativity (MMN) was tested by tDCS. Left frontal anodal tDCS significantly reduced MMN to duration and intensity deviants. Prefrontal networks supporting preattentive deviance detection vary with the kind of deviance. Abstract: Objective: To investigate the contribution of the left dorsolateral prefrontal cortex (DLPFC) to attentive and pre-attentive stimulus discrimination via transcranial direct current stimulation (tDCS). Methods: Novelty- and target-P3 as indexes of attentive stimulus discrimination and the mismatch negativities (MMNs) for duration, intensity, and frequency deviants as indexes of pre-attentive stimulus discrimination were recorded before and after delivering anodal and cathodal tDCS to the left DLPFC. Results: MMN amplitudes for all kinds of deviants decreased from pre- to post-tDCS measurement. For duration and intensity deviants, this pre-post reduction was stronger after anodal tDCS, as compared to the decrease after sham stimulation. No such modulation was found for the MMN to frequency deviants. Neither the novelty-P3 nor the target-P3 was modulated by tDCS. Conclusion: The selective MMN decrease after anodal (excitatory) stimulation of the left DLPFC suggests that this region either inhibits the processing of specific auditory changes or modulates the habituation of the MMN to certain kinds of deviances. Significance: Our finding that left frontal anodal tDCS reduces the MMN to duration and intensity deviants further highlights the contribution of frontal brain regions to MMN generation and extends previous reports of reduced MMNs to frequency deviants after right frontal anodal tDCS.